2012
DOI: 10.1002/jcc.23095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atomic charge, solvation, entropy, and ligand protonation state on MM‐PB(GB)SA binding energies of HIV protease

Abstract: The molecular mechanics-Poisson-Boltzmann surface area (MM-PBSA) and MM-generalized-Born surface area (MM-GBSA) approaches are commonly used in molecular modeling and drug design. Four critical aspects of these approaches have been investigated for their effect on calculated binding energies: (1) the atomic partial charge method used to parameterize the ligand force field, (2) the method used to calculate the solvation free energy, (3) inclusion of entropy estimates, and (4) the protonation state of the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 87 publications
4
51
0
Order By: Relevance
“…Gaussian 98 38 was used to perform geometric optimization of the inhibitor with 6-31G** basis functions, and the restrained electrostatic potential (RESP) procedure, also part of the AMBER package, was used to calculate the partial atomic charges. All ligands were found to be neutral except for Indinavir, which was protonated at pH 5, in agreement with the previous findings of Oehme et al 15 (structures for all nine inhibitors are shown in Figure 1). Before the production simulations reported here were run, all systems were minimized and equilibrated for 2 ns using the protocol defined by the BAC.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…Gaussian 98 38 was used to perform geometric optimization of the inhibitor with 6-31G** basis functions, and the restrained electrostatic potential (RESP) procedure, also part of the AMBER package, was used to calculate the partial atomic charges. All ligands were found to be neutral except for Indinavir, which was protonated at pH 5, in agreement with the previous findings of Oehme et al 15 (structures for all nine inhibitors are shown in Figure 1). Before the production simulations reported here were run, all systems were minimized and equilibrated for 2 ns using the protocol defined by the BAC.…”
Section: Methodssupporting
confidence: 91%
“…1315 Here, we use ensembles of 50 simulations to determine the variability of the results produced by these analyses and how they depend upon the replica length and rate at which conformational samples are taken from the MD trajectories. This strategy is enabled by the increasing availability of supercomputing resources with many thousands of cores (sometimes referred to as petascale resources) which make the execution of many large simulations feasible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This kind of approach typically yields overestimated binding free energy values, but they are very useful for extracting comparative trends. 62 The results, presented in Table 1, show that the Trp binding energy is doubled in the closed loop conformation (most populated state in Cf1) compared to the open-extended loop conformation observed in Cf2. Interestingly, in the open-extended loop conformation, the interaction with Thr379 is weakend and the interaction with Arg231 is almost lost.…”
Section: Resultsmentioning
confidence: 96%